1998
DOI: 10.1038/sj.bmt.1701228
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and transplantation of autologous peripheral CD34+ progenitor cells highly purified by magnetic-activated cell sorting

Abstract: Summary:Peripheral stem cells were mobilized and collected in 26 pediatric patients with malignant diseases. A total of 47 leukaphereses were performed in the 26 patients. The mean number of nucleated cells collected was 4.5 ؎ 2.6 × 10 8 /kg and the number of CD34 ؉ progenitors collected was 6.7 ؎ 6.8 × 10 6 /kg. CD34-positive selection was performed using a two-step method of magnetic-activated cell sorting (MACS) in 24 patients or a combination of an immunoaffinity column and MACS in two patients. The purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 13 publications
0
98
0
1
Order By: Relevance
“…However, the efficiency of CliniMACS in terms of CD34+ purity and T-cell reduction was comparable with that observed in previous studies. [7][8][9] The aim of HSCT in this setting is not simply to improve survival with normal enzyme activity, but also to stabilize or enhance neuropsychological function thereby promoting Table 2 Cell composition of unmanipulated bone marrow, buffy coat and positively selected product quality of life and patient independence. Therefore, prevention of the potential demyelinating effects because of toxicity and/or GVHD should be considered relevant for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficiency of CliniMACS in terms of CD34+ purity and T-cell reduction was comparable with that observed in previous studies. [7][8][9] The aim of HSCT in this setting is not simply to improve survival with normal enzyme activity, but also to stabilize or enhance neuropsychological function thereby promoting Table 2 Cell composition of unmanipulated bone marrow, buffy coat and positively selected product quality of life and patient independence. Therefore, prevention of the potential demyelinating effects because of toxicity and/or GVHD should be considered relevant for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been previously shown that the magnetic-activated cell separation technique is highly effective for clinical-scale preparation of CD34+ progenitor cells collected from leukapheresis products. [7][8][9] Large-scale preparations of purified CD34+ cells from bone marrow (BM) products have been used and reported only occasionally, as the expected cell loss has been considered too high to safely perform HSCT, particularly in adult patients. Children with IMSD have relatively low weights and often receive BM from an unrelated donor.…”
Section: Discussionmentioning
confidence: 99%
“…Presently magnetic cell sorting of peripheral blood CD34 + cells has been shown to be the most effective selection procedure in recovering high numbers of stem cells with high purity and low T cell numbers and therefore was used in our patients. [6][7][8] Donors were provided by the 'Deutsche Knochenmarsspenderdatei' (DKMS) (Tübingen, Germany). Two cell separations after mobilization with G-CSF yielded sufficient numbers of progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In the other two cases CD34 + cells were selected using the CliniMACS-system (Miltenyi Biotec). Apheresis products were diluted (1:1) in buffer solution consisting of phosphate-buffered saline (PBS) w/o Ca/Mg (Gibco, Paisley, UK), 5 mm EDTA and 5% human albumin at a final concentration of 0.8% (Immuno, Vienna, Austria) and centrifuged for 15 min at 350 g for removal of platelets.…”
Section: Magnetic Positive Selection Of Cd34 + Cellsmentioning
confidence: 99%
See 1 more Smart Citation